2016
DOI: 10.1111/1753-0407.12474
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of peripheral arterial disease in diabetes mellitus

Abstract: Peripheral arterial disease (PAD) increases the risk of lower extremity amputation. It is also an independent predictor of cardiovascular and cerebrovascular ischemic events, affecting both the quality and expectancy of life. Many studies have demonstrated that the prevalence of PAD in patients with diabetes mellitus (DM) is higher than in non-diabetic patients. In diabetic patients, PAD occurs early with rapid progression, and is frequently asymptomatic. Multiple metabolic aberrations in DM, such as advanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 89 publications
(167 reference statements)
2
59
0
2
Order By: Relevance
“…The positive association with PAD has been reported previously 41,42 and may relate to marked oxidative stress, inflammation and atherothrombosis that contribute to dyserythropoiesis and a shortened red cell lifespan in type 2 diabetes. 43 We found that anemia was a significant independent predictor of death, a result that accords with the findings of other community-based 6 and clinic-based 12 studies. The 57% increase in all-cause mortality was similar to the 49% increase found in a combined analysis of a number of UK cohorts 6 albeit this latter study did not have the range of explanatory variables that was available in FDS2.…”
Section: Discussionsupporting
confidence: 90%
“…The positive association with PAD has been reported previously 41,42 and may relate to marked oxidative stress, inflammation and atherothrombosis that contribute to dyserythropoiesis and a shortened red cell lifespan in type 2 diabetes. 43 We found that anemia was a significant independent predictor of death, a result that accords with the findings of other community-based 6 and clinic-based 12 studies. The 57% increase in all-cause mortality was similar to the 49% increase found in a combined analysis of a number of UK cohorts 6 albeit this latter study did not have the range of explanatory variables that was available in FDS2.…”
Section: Discussionsupporting
confidence: 90%
“…Diabetes is an established risk factor for LEAD [4], and the prognosis of LEAD in patients with diabetes is worse than that for those without diabetes, with a more rapid progression, wider range of vasculature lesions, and greater susceptibility to stenosis and occlusion [5]. In diabetes patients, given the common concurrence of neuropathy, LEAD often remains clinically undetected in the early stage.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, diabetes-associated LEAD is often concomitant with neuropathy [27]. The decrease in the sense of pain and temperature caused by diabetic neuropathy may conceal the symptoms of LEAD (e.g., resting pain), leading to a delayed diagnosis of LEAD and more serious outcomes such as amputations [28,29]. Considering the heavy public health and economic burden and the worse prognosis caused by diabetes-related amputations [30], early detection or exploration of an effective biomarker for LEAD is needed.…”
Section: Discussionmentioning
confidence: 99%